Analisis Leadership Terhadap Employee Performance - Robert Roya; Umban Adi Jaya (Jurnal Adijaya Multidisplin, 2023)
This study deals with the importance of employee performance. In the research area there are problems where the level of productivity has not been maximized. Leadership becomes very important to be able to play a role in employee performance. The purpose of this study is to determine the effect of leadership on employee performance. The research method used is quantitative and associative methods. The sampling technique used random sampling method, with a total of 72 respondents. Data analysis used multiple regression analysis, t test, F test, R2 test. The result of this study is that leadership influences employee performance.